Transparency in the existence, use, and output of a mental health data resource: a descriptive paper from the National Institute for Health and Care Research (NIHR) Maudsley Biomedical Research Centre (BRC) Clinical Record Interactive Search (CRIS) Platform - Jewell, Amelia; Broadbent, Matthew; Delaney-Pope, Claire; Pritchard, Megan; Woods, Hannah; Stewart, Robert (International Journal of Population Data Science, 2025)
Background Transparency in the use of routinely collected mental health data for research is essential in maintaining public support and trust, as well as for supporting the sharing of information and data resources amongst the academic community. The National Institute for Health and Care Research (NIHR) Maudsley Biomedical Research Centre (BRC) Clinical Records Interactive Search (CRIS) enables a case register of deidentified mental health records from the South London and Maudsley NHS Foundation Trust (SLaM). CRIS supports mental health research across the lifespan from children and adolescents to older adults. Aim This paper aims to describe the activities which contribute to ensuring that transparency is maintained throughout the journey of data in CRIS: from data collection, through application in research, to dissemination of findings. Approach A communications plan is in place to support Patient and Public Involvement (PPI) and transparency initiatives for all CRIS stakeholders, including patients and carers, academic users, and the general public. Activities can be divided into three categories of transparency: existence, use, and output. Discussion There are challenges to maintaining transparency, including ensuring that activities are varied enough to reach all stakeholders, including harder to reach groups, and presenting information in a way that is appropriate for the relevant audience. However, greater transparency has led to more opportunities for researchers to engage with patients and the CRIS model is widely accepted by patients. Conclusion This paper set out to describe CRIS communications and transparency activities. We believe the material covered will be of interest to other providers of routinely collected data for research.